Process Treatment of Heavy Metal Waste from Various Types of Adosorbents ( clay, flay ash, and natural zeolite) : A Review - Yuda Darmawan Efendi; Hafni Indriati Nasution; Siti Rahmah; Moondra Zubir (Indonesian Journal of Chemical Science and Technology (IJCST), 2021)
Development of the industry, especially the palm oil mill industry, it will have an impact with tangible evidence that makes the environment polluted. Heavy metals will be produced from the palm oil mill industry and will pollute the environment. Zn metal is one of the heavy metal waste produced from the mustard coconut factory industry. Zn heavy metal waste will be very dangerous if it exceeds a predetermined level and will have an impact on humans, animals and the environment. One effort to reduce heavy metals using the adsorption method. Adsorption has advantages over a variety of other methods. Adsorban that is used from materials found in nature and the resulting waste can be used as an adsorbent. The type and type of adsorbent greatly affect the pH adsorption level of the Zn metal solution.